2021
DOI: 10.3390/cancers13174478
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Safety, Feasibility and Benefits of Exercise for Patients with Advanced Cancer

Abstract: Exercise therapy is a common supportive strategy in curative cancer treatment with strong evidence regarding its positive effects on, for example, cancer-related fatigue, health- related quality of life, and physical function. In the field of advanced cancer patients, knowledge about exercise as a useful supportive strategy is missing. The aim of this systematic review was to evaluate the feasibility and safety of exercise interventions as well as its effects on lowering the symptom burden. We included randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 67 publications
0
25
0
2
Order By: Relevance
“…Equally, exercise might prevent declines in skeletal muscle mass [ 20 ] and manage cancer symptoms, increase physical function, and improve overall QoL [ 21 , 22 ]. There is evidence that aerobic and resistance exercise training (typically delivered in a structured, supervised setting) is beneficial among people with advanced cancer [ 23 ], including older adults with advanced cancer undergoing treatment [ 24 ]. Preliminary evidence from a recent randomized controlled trial in 40 patients with pancreatic cancer and cachexia also found a three month, supervised resistance training intervention may improve muscle strength and lean body mass [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, exercise might prevent declines in skeletal muscle mass [ 20 ] and manage cancer symptoms, increase physical function, and improve overall QoL [ 21 , 22 ]. There is evidence that aerobic and resistance exercise training (typically delivered in a structured, supervised setting) is beneficial among people with advanced cancer [ 23 ], including older adults with advanced cancer undergoing treatment [ 24 ]. Preliminary evidence from a recent randomized controlled trial in 40 patients with pancreatic cancer and cachexia also found a three month, supervised resistance training intervention may improve muscle strength and lean body mass [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to control the side effects of these treatments is the prescription of physical exercise [ 6 ]. Several studies have shown how physical exercise reduces the toxicity of treatment in patients with breast cancer, improving physiological and functional parameters as well as quality of life [ 7 , 8 , 9 ]. As supported by the International Agency for Research on Cancer (IARC), a physical exercise regimen can be routinely prescribed to women with breast cancer both during treatment and afterwards, although they must meet a series of characteristics [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eine enge Anbindung an das medizinische Behandlungsteam ist wichtig, um Kenntnisse über den aktuellen Gesundheitszustand der Patienten zu erlangen, unerwünschte Ereignisse zu vermeiden und ein sicheres Training zu ermöglichen. Am Universitätsklinikum Essen traten bisher keine unerwünschten Ereignisse in diesem Projekt auf, was im Einklang mit der Literatur über Bewegungsinterventionen in der pädiatrischen Onkologie 6 und bei erwachsenen Patienten mit fortgeschrittener Krebserkrankung 7 steht und zeigt, dass ein sicheres Training auch für diese besondere Patientengruppe möglich ist.…”
Section: Interventionenunclassified